A Comparative Analysis of the Determinants of Bank Profitability: The Roles of Liquidity and Leverage in Indonesia and Thailand, 2015–2024 - Adinda Rahma Hashifa; Dian Pratiwi, Ririh (E-Jurnal Akuntansi, 2026)
Bank profitability in Indonesia and Thailand fluctuated differently during the 2015–2024 period, particularly during the pandemic and the subsequent recovery, while prior empirical findings remain inconsistent. This study compares the effects of liquidity and leverage on bank profitability while controlling for firm size. Annual data from conventional banks in Indonesia and Thailand were analysed using multiple linear regression. The results indicate that profitability in Indonesia is influenced by leverage and firm size, whereas in Thailand it is affected by liquidity, leverage, and firm size. The novelty of this study lies in its comparative analysis of Indonesia and Thailand over the 2015–2024 period. It also extends previous research by focusing on conventional banks and incorporating firm size as a control variable. This study contributes to the ASEAN banking literature and offers strategic implications for both management and regulators.